Release film

JP2024091669A5Inactive Publication Date: 2025-01-20MITSUBISHI CHEM CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024060691
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-04-04
Publication Date
2025-01-20
Estimated Expiration
Not applicable · inactive patent
Patent Text Reader

Abstract

To provide a new release film concerning a polyester film that is used for applications for transferring a resin and transferring a surface state of a polyester film, which is excellent in releasability to various resins, prevents a resin component from being transferred to a surface of a transfer resin, and can satisfactorily treat secondary working for the surface of the transfer resin.SOLUTION: A release film has a release layer formed of a release layer formation composition on at least one surface side of a polyester film, in which a content of a release agent is less than 15 mass% as a ratio of the content in the total non-volatile component in the release layer formation composition, and a content of the release agent in the release layer is 3.4 mg / m2 or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a release film comprising a release layer on at least one surface of a polyester film. [Background technology]

[0002] Polyester films, typified by polyethylene terephthalate and polyethylene naphthalate, have excellent properties such as mechanical strength, dimensional stability, flatness, heat resistance, chemical resistance, optical properties, etc., and are also excellent in cost performance, and therefore are used for various applications.

[0003] Examples of applications of polyester films include process films used in various processes, such as electromagnetic wave shielding applications, transfer applications such as simultaneous transfer applications during molding, manufacturing of flexible printed wiring boards, process papers for manufacturing plastic sheets, etc. When used for these applications, a method has been proposed in which a release coating film is laminated on the surface of the polyester film to obtain releasability against various resins and adhesives.

[0004] In plasma displays (PDPs) and the like, an electromagnetic wave shielding film, i.e., a conductive film, is attached to the front of the display panel. A conductive film made of polyester film with a mesh-like metal wire is commonly used as this electromagnetic wave shielding film.

[0005] This type of electromagnetic wave shielding film is formed on a support film, and then the film is pressed at high temperature onto the surface of various devices to transfer the electromagnetic wave shielding film. Conventionally, a flat polyester film has generally been used as the support film for such a transfer-type electromagnetic shielding film, but in order to give the product a matte appearance, it has been proposed to use a polyester film with a matte surface as the support film and transfer this matte surface to the product.

[0006] In simultaneous molding and transfer, a transfer foil is generally used, which is made up of a hard coat layer, a pattern printed layer, an adhesive layer, and other transfer layers laminated in sequence on a release layer of a support film. This transfer foil is set in a mold for injection molding, and a transfer foil sheet is bonded integrally to the surface of a resin molded product while the resin molded product is being molded, and the design is transferred to the resin molded product to decorate it; this is the so-called in-mold transfer method. Even in such an in-mold transfer method, a molded product having a low gloss may be required as one of the design features of the molded product. As a means for imparting a low gloss to a molded product, a method of using a polyester film with a matte surface as the support film and transferring this matte surface to the product can be given.

[0007] For example, Patent Document 1 discloses a release film having a release layer on at least one film surface, the release layer containing a release agent, a thermosetting compound, and a binder polymer, and in which the peel strength between the release layer and an acrylic adhesive tape around 100% elongation is within a specific range.

[0008] For example, Patent Document 2 discloses an adhesive release polyester film for in-mold transfer materials, which has an adhesive release layer on at least one side of a polyester film, the adhesive release layer containing a fluorine-based polymer having a glass transition temperature of -40°C or more and 20°C or less, a urethane-based polymer having a glass transition temperature of -60°C or more and 10°C or less, and a crosslinking agent, the peel force of a hard coat layer from the adhesive release layer being 0.2 N / mm or more and 0.4 N / mm or less, and the surface hardness of the adhesive release layer being 0.5 GPa or more and 4.5 GPa or less as measured by a microhardness meter.

[0009] Patent Document 3 discloses a biaxially oriented polyester film for release, which has a polyester A layer containing inorganic particles and / or organic particles as at least one outermost layer, the average surface roughness Ra of the outermost polyester A layer surface being 0.38 μm or more and 1.0 μm or less, the average length RSm of the roughness curve element of the polyester A layer surface being 10 μm or more and 80 μm or less, and the release layer having a composition containing a fluorine-based polymer. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] JP 2010-247456 A [Patent Document 2] JP 2012-11658 A [Patent Document 3] JP 2016-175229 A Summary of the Invention [Problem to be solved by the invention]

[0011] As described above, by providing a release layer on the surface of the polyester film, it is possible to maintain releasability against various resin layers, and it becomes possible to use it as a polyester film for transfer. In addition, when the surface of the polyester film is roughened to form a matte finish, the surface of the polyester film is pressed against the surface of an object and then pressed, and the polyester film is then peeled off, whereby the roughened surface state is transferred to the surface of the object, resulting in a matte finish.

[0012] In the conventionally proposed polyester film for transfer, a large amount of a release agent must be added to the release layer to give the layer a release property. However, when such a release layer is used, the release component is transferred to the transferred resin surface, which may change the properties of the transferred resin layer surface, or may make it difficult to perform secondary processing such as providing a protective layer or an adhesive layer on the resin layer surface.

[0013] Therefore, the present invention relates to a polyester film used for transferring a resin layer or transferring the surface state of a polyester film, and aims to provide a new release film that has excellent release properties for various resin layers, is less susceptible to transfer of release components onto the surface of the transferred resin layer, and allows for good secondary processing of the surface of the transferred resin layer. [Means for solving the problem]

[0014] The present invention provides a polyester film having a release layer formed from a release layer-forming composition on at least one side thereof, the release agent being less than 15 mass % as a proportion of the total non-volatile components in the release layer-forming composition, and the content of the release agent in the release layer being 3.4 mg / m 2 The present invention proposes a release film characterized by the above. Effect of the Invention

[0015] The release film proposed by the present invention has a release agent content of 3.4 mg / m 2 For the above reasons, it is possible to effectively peel off various resin layers, and by making the release agent less than 15 mass% as a proportion of all non-volatile components in the release layer-forming composition, it is possible to reduce the amount of release component transferred to the resin layer surface, and secondary processing of the resin layer surface can be performed smoothly. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Next, the present invention will be described based on an embodiment, however, the present invention is not limited to the embodiment described below.

[0017] <<Release film>> A release film according to one embodiment of the present invention (referred to as "this release film") comprises a release layer (referred to as "this release layer") formed from a release layer-forming composition on at least one side of a polyester film (referred to as "this polyester film") as a substrate, the release agent is less than 15 mass% as a proportion of the total non-volatile components in the release layer-forming composition, and the content of the release agent in the release layer is 3.4 mg / m 2 That is all. The laminated structure of the present release film may be a structure in which a release layer is formed on one side of the present polyester film and the surface of the polyester film substrate is left as is on the other side, or a structure in which another layer is formed on the other side. Also, a structure in which release layers are formed on both sides of the present polyester film may be used. Furthermore, other layers may be provided between the polyester film and the release layer. However, the release layer is preferably on at least one outermost surface of the polyester film.

[0018] <<This polyester film>> The polyester film serves as the substrate for the release film. The polyester film may be a non-stretched film (sheet) or a stretched film. Of these, a uniaxially or biaxially stretched film is preferred. Of these, a biaxially stretched film is preferred in terms of excellent balance of mechanical properties and flatness.

[0019] The polyester film may be a single layer or a multi-layer of two or more layers, and is not particularly limited. In order to impart a low gloss feeling to the surface of the transfer resin layer, the release film is preferably one having a matte surface shape. As a method for imparting a matte tone, a structure having a particle-containing layer containing particles can be mentioned.

[0020] The polyester film may be configured to have only a layer that does not contain particles, to have only a particle-containing layer that contains particles, or to have a particle-containing layer on one or both sides of a base layer. Specific examples of the configuration having a particle-containing layer on one or both sides may include a configuration having a particle-containing layer A on both sides of a base layer, a configuration having a particle-containing layer A on one side of the base layer and a particle-containing layer B different from the particle-containing layer A formed on the other side of the base layer, a configuration having a particle-containing layer A on one side of the base layer and no layer formed on the other side of the base layer, or a configuration having a particle-containing layer A on one side of the base layer and a layer not containing particles formed on the other side of the base layer. The present polyester film preferably has a configuration including a particle-containing layer A, and particularly preferably has a configuration including a particle-containing layer A on one side of a base layer and a particle-containing layer B different from the particle-containing layer A on the other side of the base layer, which will be described in detail later.

[0021] (Genuine polyester) The layers constituting the present polyester film, for example the above-mentioned base layer, particle-containing layer A, particle-containing layer B and other layers, are preferably layers containing polyester as a main component resin. The polyester that is the main component resin of the present polyester film (also referred to as "the present polyester") may be either a homopolyester or a copolymer polyester. When the surface of the present release film is roughened to have a matte finish, the present polyester is preferably a copolymer polyester containing a copolymer component. Among them, polyethylene terephthalate containing a copolymer component (referred to as "copolymerized polyethylene terephthalate") is more preferable. Here, the term "main component resin" refers to the resin that is contained in the largest proportion among the resin components that constitute each layer.

[0022] The polyester may be any polyester obtained by polycondensation of an aromatic dicarboxylic acid and an aliphatic glycol. Examples of the aromatic dicarboxylic acid include terephthalic acid and 2,6-naphthalenedicarboxylic acid, and examples of the other aliphatic glycol include ethylene glycol, diethylene glycol, and 1,4-cyclohexanedimethanol. Representative polyesters include polyethylene terephthalate (PET) and polyethylene-2,6-naphthalenedicarboxylate (PEN), with polyethylene terephthalate being preferred.

[0023] Examples of the dicarboxylic acid component of the copolymerized polyester and copolymerized polyethylene terephthalate include one or more selected from isophthalic acid, phthalic acid, terephthalic acid, 2,6-naphthalenedicarboxylic acid, adipic acid, sebacic acid, and oxycarboxylic acids (e.g., p-oxybenzoic acid), and examples of the other glycol component include one or more selected from ethylene glycol, diethylene glycol, propylene glycol, butanediol, 1,4-cyclohexanedimethanol, and neopentyl glycol. In particular, the copolymerization component of the copolymerized polyethylene terephthalate is preferably a copolymerization component that gives the copolymerized polyethylene terephthalate a melting point of 240°C or less, more preferably a copolymerization component that gives the copolymerized polyethylene terephthalate a melting point of 235°C or less, and even more preferably a copolymerization component that gives the copolymerized polyethylene terephthalate a melting point of 230°C or less. By making the melting point of the copolymerized polyethylene terephthalate 240°C or less, when a layer containing the copolymerized polyethylene terephthalate is stretched and heat-treated, protrusions having a relatively large height are likely to appear on the surface of the layer, and a film having sufficiently low gloss can be obtained, which is preferable. In order to make the melting point 240° C. or less, the dicarboxylic acid component of the copolymerized polyethylene terephthalate preferably contains one or more selected from isophthalic acid, phthalic acid, sebacic acid, etc., and the glycol component preferably contains one or more selected from diethylene glycol, propylene glycol, butanediol, etc. In particular, from the viewpoint of efficiently lowering the melting point and facilitating synthesis of copolymerized polyethylene terephthalate, it is preferable for the dicarboxylic acid component of the copolymerized polyethylene terephthalate to contain isophthalic acid.

[0024] (base material layer) The base layer of the present polyester film is the layer having the greatest thickness among all the layers constituting the present polyester film, and its composition is arbitrary so long as it contains the above-mentioned polyester as the main component resin.

[0025] The base layer may include a layer containing particles, or may consist of only a layer containing particles, although from the viewpoint of cost, it is preferable that the base layer is a layer that does not contain particles such as organic particles or inorganic particles described below.

[0026] From the viewpoint of preventing curling of the polyester film, the thickness of the base layer is preferably 60 to 100% of the thickness of the polyester film, more preferably 65% ​​or more or 99% or less, and even more preferably 70% or more or 99% or less. When the thickness is in this range, the base layer itself has stiffness, so that the polyester film is less likely to curl.

[0027] (Particle-containing layer) The polyester film preferably has a particle-containing layer that contains particles in order to impart low gloss and easy lubricity. In particular, a preferred configuration has a particle-containing layer A on one side of a base layer and a particle-containing layer B different from the particle-containing layer A on the other side of the base layer. The preferred structures of the particle-containing layer A and the particle-containing layer B described below also correspond to the preferred structures of the particle-containing layer in the present polyester film.

[0028] (particle) The particles are not particularly limited as long as they can impart a matte finish. For example, they may be inorganic particles, organic particles, or crosslinked polymer particles. Inorganic particles are preferred because they may form voids in the film when stretched, and therefore do not require the addition of a white pigment to improve visibility, while organic particles are preferred because they are less likely to form voids, and therefore do not reduce the strength of the film.

[0029] Examples of inorganic particles include silica, calcium carbonate, kaolin, talc, magnesium carbonate, barium carbonate, calcium sulfate, barium sulfate, lithium phosphate, calcium phosphate, magnesium phosphate, aluminum oxide, silicon oxide, titanium oxide, zirconium oxide, lithium fluoride, calcium fluoride, lithium fluoride, zeolite, and molybdenum sulfide. The silica particles may contain, in addition to silicon dioxide (SiO2), for example, hydrous silicon dioxide.

[0030] Examples of organic particles include acrylic resin, styrene resin, urea resin, phenol resin, epoxy resin, and benzoguanamine resin. Among them, particles made of resins containing methyl methacrylate or styrene or both as copolymerization components are particularly preferred because they are compatible with PET films. In addition, organic particles such as polytetrafluoroethylene, benzoguanamine resin, thermosetting epoxy resin, unsaturated polyester resin, thermosetting urea resin, and thermosetting phenol resin may be used.

[0031] Examples of crosslinked polymer particles include copolymers of crosslinkable monomers such as divinylbenzene and polyacrylate with styrene, acrylic acid, methacrylic acid, derivatives of acrylic acid or methacrylic acid, and other various vinyl monomers.

[0032] The shape of the particles is arbitrary. For example, it may be any of spherical, blocky, rod-like, flat, etc. However, from the viewpoint of obtaining a uniform matte surface, it is preferable that the particles are spherical. There is no particular restriction on the hardness, specific gravity, color, etc. of the particles, and two or more different types may be used in combination.

[0033] (Particle-containing layer A) The particle-containing layer A is preferably a layer containing particles X having an average particle size of 2.0 μm to 10.0 μm, and is preferably a layer on the surface of which a release layer, which will be described later, is provided.

[0034] By containing particles X having an average particle size of 2.0 μm or more in the particle-containing layer A, the surface of the particle-containing layer A can be roughened and made matte. However, if the particles X are too large, the pressure rise in the filter in the polyester extrusion process during film production may become large, resulting in reduced productivity. Therefore, the average particle size of the particles X is preferably 2.0 μm or more, and more preferably 10.0 μm or less, and even more preferably 3.0 μm or more or 9.0 μm or less, and even more preferably 4.0 μm or more or 8.0 μm or less.

[0035] When the particles are in the form of a powder, the average particle size of the particles can be determined by measuring the powder using a centrifugal sedimentation particle size distribution analyzer (e.g., Model SA-CP3 manufactured by Shimadzu Corporation) and determining the particle size at an accumulated volume fraction of 50% (d50) in the equivalent sphericity distribution. The average particle size of particles in a film, layer, or resin can be determined by observing 10 or more particles with a scanning electron microscope (SEM) to measure the diameters of the particles and calculating the average value. In this case, in the case of non-spherical particles, the average value of the longest diameter and the shortest diameter can be measured as the diameter of each particle. The same applies to the particles described below.

[0036] The particles X are not particularly limited as long as they are particles capable of imparting a matte finish, and may be, for example, the above-mentioned inorganic particles, organic particles, or crosslinked polymer particles.

[0037] The particles X contained in the particle-containing layer A are preferably particles with a small true specific gravity. If the true specific gravity is small, the number of particles can be relatively increased. In other words, the number of particles can be increased with the same size and content (mass%), and the number of protrusions on the surface of the particle-containing layer A, in other words, the density, can be increased, and the low gloss feeling can be further improved. From this viewpoint, the true specific gravity of the particles X contained in the particle-containing layer A is preferably 2.0 or less, more preferably 1.5 or less, and even more preferably 1.3 or less, with the lower limit being about 0.5.

[0038] From the viewpoint of roughening the surface of the particle-containing layer A to give it a matte finish, it is preferable that the true specific gravity of the particles X contained in the particle-containing layer A is 2.0 or less and the average particle size is in the range of 2.0 to 10.0 μm.

[0039] The content of particles X in the particle-containing layer A is preferably 0.1 to 20 mass% in the particle-containing layer A (100 mass%) from the viewpoints of being able to suitably roughen the surface of the particle-containing layer A and preventing breakage or the like during film stretching, and is more preferably 1 mass% or more or 18 mass% or less, more preferably 2 mass% or more or 15 mass% or less, more preferably 3 mass% or more or 13 mass% or less, and even more preferably 5 mass% or more or 10 mass% or less.

[0040] The polyester A constituting the main component resin of the particle-containing layer A may be either a homopolyester or a copolymer polyester containing a copolymer component.

[0041] It is preferable that the copolymerization component is contained in an amount of 0.1 to 10 mol % based on the total amount of polyester constituting the particle-containing layer A. If the copolymerization component is contained in an amount of 0.1 mol % or more, the particle-containing layer A can be softened, and the height of the protrusions on the surface of the particle-containing layer A can be increased. On the other hand, if the copolymerization component is contained in an amount of 10 mol % or less, the film can be efficiently produced without breakage, which is preferable. In addition, when the present laminated polyester film is a stretched film, it is preferable that the proportion of the copolymerization component is within the above range, since stretch orientation and heat fixation are possible. From this viewpoint, the copolymerization component is preferably contained in an amount of 0.1 to 10 mol % relative to the total amount of polyester constituting the particle-containing layer A, more preferably 1 mol % or more or 8 mol % or less, and even more preferably 3 mol % or more or 6 mol % or less.

[0042] In general, when polyester is produced (polycondensed) using ethylene glycol as one of the raw materials, a part of the ethylene glycol is modified to become diethylene glycol, which is introduced into the polyester skeleton. This diethylene glycol is called by-product diethylene glycol, and the amount of the by-product varies depending on the type of polycondensation (ester exchange method, direct polycondensation), but is about 1 to 5 mol% of the ethylene glycol. In the present invention, diethylene glycol produced as a by-product from ethylene glycol is not treated as a copolymerization component.

[0043] A preferred embodiment of the particle-containing layer A, which makes it possible to maintain the productivity of the present release film while further improving the low gloss feeling of the surface of the present release film, is one in which the true specific gravity of the particles X in the particle-containing layer A is 2.0 or less, the average particle size of the particles X is 2.0 to 10.0 μm, and the copolymerization component is contained in an amount of 0.1 to 10 mol % relative to the total amount of the polyester constituting the particle-containing layer A.

[0044] The thickness of the particle-containing layer A is preferably 1.0 to 20 μm, more preferably 2.0 μm or more or 20 μm or less, even more preferably 3.0 μm or more or 20 μm or less, and even more preferably 4.0 μm or more or 15 μm or less. A matte finish can be effectively imparted by making the thickness of the particle-containing layer A 1.0 μm or more. Even if the thickness of the particle-containing layer A exceeds 20 μm, the effect of improving the matte finish remains almost the same.

[0045] (Particle-containing layer B) As described above, a particle-containing layer A can be provided on one side of the base layer, and a particle-containing layer B different from the particle-containing layer A can be formed on the other side of the base layer as a layer that does not have a release layer, which will be described later.

[0046] In this case, it is preferable that the particle-containing layer B also contains particles X having an average particle size of 2.0 to 10.0 μm, in order to prevent curling of the entire polyester film. However, since the surface of the particle-containing layer B only needs to be roughened to an extent that makes it easy to handle, it does not need to be as rough as the surface of the particle-containing layer A. Therefore, the content of particles X having an average particle size of 2.0 to 10.0 μm may be less than that of the particle-containing layer A. Specifically, the content of particles X in particle-containing layer B is preferably 0.1 to 100% by mass of the content of particles X in particle-containing layer A, more preferably 1% by mass or more or 95% by mass or less, and even more preferably 5% by mass or more or 90% by mass or less.

[0047] The particle-containing layer B may contain particles Y having an average particle size of less than 2.0 μm in order to whiten the polyester film. In this case, the particle-containing layer B may contain particles Y without containing particles X, or may contain particles Y together with particles X. When particles Y are contained together with particles X, the mass ratio of particles X to particles Y is preferably 1:99 to 99:1, more preferably 10:90 to 90:10, and even more preferably 15:85 to 85:15.

[0048] The shape of the particles Y is arbitrary. For example, it may be any of spherical, blocky, rod-like, flat, etc. However, from the viewpoint of preventing the formation of coarse protrusions due to aggregation, the particles Y are preferably spherical. There are no particular limitations on the hardness, specific gravity, color, etc. of the particles Y, and two or more different types may be used in combination.

[0049] From the viewpoint of imparting white opacity through a light scattering effect, the average particle size of the particles Y is preferably 0.05 μm to 0.50 μm, more preferably 0.10 μm or more or 0.45 μm or less, even more preferably 0.20 μm or more or 0.40 μm or less, and even more preferably 0.25 μm or more.

[0050] The particles Y are preferably metal compound particles from the viewpoint of imparting white opacity through a light scattering effect. Examples of metal compound particles include titanium oxide, calcium carbonate, barium sulfate, magnesium carbonate, barium carbonate, calcium sulfate, calcium phosphate, magnesium phosphate, kaolin, aluminum oxide, and zirconium oxide, and among these, metal compound particles such as titanium oxide, calcium carbonate, and barium sulfate can be mentioned.

[0051] The polyester constituting the main component resin of the particle-containing layer B may be the same as or different from the polyester constituting the main component resin of the particle-containing layer A. In other words, it may be a copolymer polyester containing a copolymer component, or a homopolyester containing no copolymer component. In particular, when the polyester constituting the particle-containing layer B contains the same copolymerization component as the polyester constituting the particle-containing layer A, it is preferable that the content of the copolymerization component of the polyester constituting the particle-containing layer B is lower than the content of the copolymerization component of the polyester constituting the particle-containing layer A. In other words, it is preferable that the content of the copolymerization component of the polyester constituting the particle-containing layer A is higher than the content of the copolymerization component of the polyester constituting the particle-containing layer B. This is because, in the case of a configuration in which a release layer is provided on the surface of the particle-containing layer A, the surface on the particle-containing layer B side does not need to be as rough as the surface on the particle-containing layer A side. In this case, the difference between the content ratio of the copolymerization component relative to the total amount of polyester constituting the particle-containing layer A and the content ratio of the copolymerization component relative to the total amount of polyester constituting the particle-containing layer B is preferably 5 mol % or less, more preferably 4 mol % or less, and even more preferably 3 mol % or less. When the content ratio of the copolymerization component satisfies the above range, not only curling can be suppressed, but also adhesion between the particle-containing layer B and other layers, such as a hard coat layer, can be improved when the other layers are further laminated.

[0052] From the viewpoint of preventing curling of the polyester film, the thickness of the particle-containing layer B is preferably the same as that of the particle-containing layer A. From this viewpoint, the thickness of the particle-containing layer B is also preferably 1.0 to 20 μm, more preferably 2.0 μm or more or 20 μm or less, even more preferably 3.0 μm or more or 20 μm or less, and even more preferably 4.0 μm or more or 15 μm or less.

[0053] (Other Ingredients) Each layer constituting the polyester film base may contain, as necessary, a conventionally known weathering agent, light resistance agent, light shielding agent, antioxidant, heat stabilizer, lubricant, antistatic agent, fluorescent brightener, dye, pigment, etc. Depending on the application, an ultraviolet absorbing agent, particularly a benzoxazinone ultraviolet absorbing agent, may be contained.

[0054] <Thickness of this polyester film> The thickness of the polyester film is not particularly limited as long as it is within a range that allows film formation. In particular, from the viewpoints of mechanical strength, handling property, productivity, etc., it is preferably 1 μm to 300 μm, more preferably 5 μm or more or 125 μm or less, more preferably 8 μm or more or 100 μm or less, and even more preferably 12 μm or more or 75 μm or less.

[0055] <Main release layer> The present release film is provided with a release layer formed from a release layer-forming composition on at least one side of the present polyester film, the release agent being less than 15 mass% as a proportion of the total non-volatile components in the release layer-forming composition, and the content of the release agent in the release layer is 3.4 mg / m 2 That is all.

[0056] (Formation of the release layer) The release layer is preferably provided on at least one surface of the polyester film, particularly on the surface of the particle-containing layer A, i.e., the roughened surface, and is preferably formed by using a coating and stretching method (in-line coating), although the method is not limited to this.

[0057] As the coating and stretching method (in-line coating), for example, in the case of sequential biaxial stretching, it is preferable to coat the "release layer-forming composition" after the first stage of stretching is completed and before the second stage of stretching. In this way, coating can be performed simultaneously with stretching, and the thickness of the release layer can be made thin according to the stretching ratio, so that a film suitable as a polyester film can be produced.

[0058] Examples of a method for applying a coating liquid comprising a release layer-forming composition include air doctor coating, blade coating, rod coating, bar coating, knife coating, squeeze coating, impregnation coating, reverse roll coating, transfer roll coating, gravure coating, kiss roll coating, cast coating, spray coating, curtain coating, calendar coating, and extrusion coating.

[0059] More specifically, for example, in the case of successive biaxial stretching, a method in which a coating liquid consisting of a release layer-forming composition is coated on a uniaxially stretched film that has been particularly stretched in the longitudinal direction (machine direction), and then the film is stretched in the transverse direction to form a polyester film is excellent. According to this method, since the polyester film and the release layer can be formed simultaneously, there is an advantage in terms of production costs, and since stretching is performed after coating, the thickness of the release layer can be changed by the stretching ratio, and thin film coating can be performed more easily than offline coating.

[0060] In addition, by providing a release layer on the polyester film before stretching, the release layer can be stretched together with the polyester film, and the release layer can be firmly attached to the polyester film. Furthermore, in the production of biaxially stretched polyester films, the film can be restrained in the longitudinal and lateral directions by stretching while holding the film ends with clips or the like, and high temperatures can be applied in the heat setting step while maintaining the flatness without wrinkles or the like. Therefore, the heat treatment performed after coating can be performed at a high temperature that cannot be achieved by other methods, which improves the film-forming properties of the release layer and enables the release layer and polyester film to adhere more firmly to each other, thereby resulting in a stronger release layer.

[0061] Regardless of whether the release layer is formed by off-line coating or in-line coating, a heat treatment and irradiation with active energy rays such as ultraviolet light may be used in combination as necessary. In order to improve the coatability and adhesiveness of the coating solution for forming the release layer to the polyester film, the polyester film may be subjected to a surface treatment such as a chemical treatment, corona discharge treatment, plasma treatment, ozone treatment, chemical treatment, or solvent treatment before coating.

[0062] The release layer-forming composition, i.e., the coating liquid, may include a resin composition containing a release agent, a crosslinking agent, and various polymers.

[0063] The "release agent" to be incorporated in the release layer-forming composition is not particularly limited, and any conventionally known release agent can be used. Examples of the release agent include wax, a compound containing a long-chain alkyl group, a fluorine compound, and a silicone compound. Among these, wax and compounds containing long-chain alkyl groups are preferred from the viewpoint of low possibility of contamination when applied to optical applications, and wax is preferred from the viewpoint of low reduction in surface free energy and excellent wettability with respect to the processed layer.

[0064] The wax may include natural wax, synthetic wax, and modified wax. Natural waxes include vegetable waxes, animal waxes, mineral waxes and petroleum waxes. Examples of vegetable waxes include candelilla wax, carnauba wax, rice wax, wood wax, and jojoba oil. Examples of animal waxes include beeswax, lanolin, and spermaceti, etc. Examples of mineral waxes include montan wax, ozokerite, and ceresin, etc. Petroleum waxes include paraffin wax, microcrystalline wax, and petrolactam. Synthetic waxes include synthetic hydrocarbons, modified waxes, hydrogenated waxes, fatty acids, acid amides, amines, imides, ester waxes and ketones.

[0065] Examples of synthetic waxes include Fischer-Tropsch wax (also known as Sasol wax), polyethylene wax, etc. In addition, the following polymers, which are low molecular weight polymers (specifically, polymers with number average molecular weights of 500 to 20,000), can be mentioned: polypropylene, ethylene-acrylic acid copolymer, polyethylene glycol, polypropylene glycol, and block or graft bond of polyethylene glycol and polypropylene glycol.

[0066] Examples of modified waxes include montan wax derivatives, paraffin wax derivatives, and microcrystalline wax derivatives. The derivatives are compounds obtained by any of the following processes: refining, oxidation, esterification, and saponification, or a combination thereof. Examples of hydrogenated waxes include hydrogenated castor oil and hydrogenated castor oil derivatives.

[0067] Among these, from the viewpoint of excellent release performance, the release agent in the release layer is preferably a synthetic wax, more preferably a polyethylene wax, and even more preferably an oxidized polyethylene wax. The number average molecular weight of the synthetic wax is usually 500 to 30,000, preferably 1,000 to 15,000, and more preferably 2,000 to 8,000, from the viewpoints of suppressing transfer of the release component and of ease of handling.

[0068] In addition, when the release layer is formed, taking into consideration the fact that heating is performed for crosslinking, etc., among the above waxes, those having a melting point or softening point of 80° C. or higher, particularly 110° C. or higher, are preferred. From the viewpoint of controlling the release performance after heat treatment, the wax is preferably 200° C. or lower, particularly 170° C. or lower, particularly 150° C. or lower. The melting point of the wax can be measured by differential scanning calorimetry (DSC).

[0069] The release agent is preferably less than 15% by mass as a proportion of all non-volatile components in the release layer forming composition. By making the release agent less than 15% by mass as a proportion of all non-volatile components in the release layer forming composition, transfer of the release components can be suppressed. The proportion of the release agent is preferably less than 15% by mass, more preferably 1% by mass or more or 13% by mass or less, even more preferably 3% by mass or more or 11% by mass or less, even more preferably 5% by mass or more or 9% by mass or less. The lower limit of the content is not particularly limited, but is usually about 0.05% by mass.

[0070] The proportion of the release agent in the release layer can be calculated, for example, by the following thermogravimetric analysis (using data on thermal weight loss). When calculated by the following method, the release agent is preferably contained in the release layer in an amount of less than 15% by mass, more preferably 1% by mass or more or 14% by mass or less, even more preferably 3% by mass or more or 12% by mass or less, and even more preferably 5% by mass or more or 10% by mass or less. The lower limit of the content is not particularly limited, but is usually about 0.05% by mass. Thermogravimetric analysis method: The weight loss rate of each material constituting the release layer is measured by thermogravimetric analysis at a heat treatment temperature in the film production, for example, 230 to 250° C. The content of each component in the release layer-forming composition is multiplied by the weight loss rate obtained to determine the content of each component in the release layer, and the content ratio of the release agent is determined from the content of each component obtained.

[0071] The ratio of the release agent in the release layer can be regarded as synonymous with the ratio of the release agent to the total non-volatile components in the release layer-forming composition described above. Therefore, the present release film has a release layer on at least one side of a polyester film, the release agent is contained in the release layer in an amount of less than 15 mass %, and the content of the release agent in the release layer is 3.4 mg / m 2 It can also be regarded as a release film having the above properties. Furthermore, a release layer is provided on at least one side of the polyester film, the release layer contains a release agent at a ratio of less than 15 mass %, and the content of the release agent in the release layer is 3.4 mg / m 2 The release film described above is included in one embodiment of the present invention.

[0072] The content of the release agent in the release layer is 3.4 mg / m 2 The content of the release agent in the release layer is preferably 3.4 mg / m or more. 2 By setting the content of the release agent in the release layer at 3.4 mg / m or more, it is possible to maintain good release performance, including the balance of properties before and after the heat treatment. 2 More than 4.0 mg / m is preferable. 2 Above 4.5 mg / m 2 Above 5.0 mg / m 2More preferably, it is equal to or greater than this. There is no particular upper limit, but it is usually 1000 mg / m 2 The following is the result. The content of the release agent in the release layer can be calculated, for example, by using the above-mentioned thermogravimetric analysis method. In addition, the content of the release agent in the release layer can be adjusted, for example, by adjusting the content ratio of the release agent in the release layer-forming composition or the coating amount of the release layer-forming composition.

[0073] The proportion of the release agent in the release layer and the content of the release agent in the release layer can be determined, for example, by subjecting the surface of the release film to an X-ray photoelectron spectrometer (ESCA), a Fourier transform infrared spectrometer (FT-IR) ATR method, or a time-of-flight secondary ion mass spectrometer (TOF-SIMS). Alternatively, the release layer can be dissolved and extracted in a solvent, separated by chromatography, and then the structure can be analyzed by proton nuclear magnetic resonance spectroscopy (1H-NMR), carbon nuclear magnetic resonance spectroscopy (13C-NMR), or a Fourier transform infrared spectrometer (FT-IR), and then pyrolysis gas chromatography mass spectrometry (GC-MS).

[0074] From the viewpoint of increasing the strength of the release layer to make the layer less susceptible to transfer of the release component, it is preferable to contain a crosslinking agent in the release layer-forming composition. When the release layer is formed by crosslinking the crosslinking agent, the formed release layer contains a compound derived from the crosslinking agent as described above.

[0075] As the crosslinking agent, a conventionally known material can be used. For example, melamine compounds, oxazoline compounds, isocyanate compounds, epoxy compounds, carbodiimide compounds, silane coupling compounds, hydrazide compounds, and aziridine compounds can be mentioned. Among them, melamine compounds, oxazoline compounds, isocyanate compounds, epoxy compounds, and carbodiimide compounds are preferred. From the viewpoint of further strengthening the strength of the release layer and improving the adhesion to the film of the substrate, melamine compounds are particularly preferred.

[0076] The melamine compound is a compound having a melamine skeleton in the compound, and for example, an alkylolated melamine derivative, a compound partially or completely etherified by reacting an alkylolated melamine derivative with an alcohol, and a mixture thereof can be used. Examples of alkylolation include methylolation, ethylolation, isopropylolation, n-butyrolation, and isobutyrolation, and from the viewpoint of reactivity, methylolation is preferred. In addition, as the alcohol used for etherification, methyl alcohol, ethyl alcohol, isopropyl alcohol, n-butanol, isobutanol, etc. are preferably used. From the viewpoint of improving the coating film strength and facilitating the formation of a fine protrusion structure, a partially etherified alkylolated melamine derivative is preferred, and an alkylol etherified with methyl alcohol is more preferred. In addition, the melamine compound may be either a monomer or a polymer of dimer or more, or a mixture thereof may be used. Furthermore, a compound obtained by co-condensing a part of melamine with urea or the like can also be used.

[0077] Specific examples of the polymer include polyester resin, acrylic resin, urethane resin, polyvinyl (polyvinyl alcohol, vinyl chloride vinyl acetate copolymer, etc.), polyalkylene glycol, polyalkyleneimine, methyl cellulose, hydroxycellulose, starches, etc. Among these, polyester resin and urethane resin are preferred in that the releasability can be easily controlled, and polyester resin is more preferred in that it enhances adhesion to the polyester film, suppresses transfer of the release component, and allows control of the balance of release performance before and after heat treatment.

[0078] The polyester resin may be composed of, for example, the following polyvalent carboxylic acid and polyvalent hydroxy compound as main components. That is, as the polyvalent carboxylic acid, terephthalic acid, isophthalic acid, orthophthalic acid, phthalic acid, 4,4'-diphenyldicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 2-potassium sulfoterephthalic acid, 5-sodium sulfoisophthalic acid, adipic acid, azelaic acid, sebacic acid, dodecanedicarboxylic acid, glutaric acid, succinic acid, trimellitic acid, trimesic acid, pyromellitic acid, trimellitic anhydride, phthalic anhydride, p-hydroxybenzoic acid, trimellitic acid monopotassium salt, and ester-forming derivatives thereof may be used. As the polyvalent hydroxy compound, Ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, 2-methyl-1,5-pentanediol, neopentyl glycol, 1,4-cyclohexanedimethanol, p-xylylene glycol, bisphenol A-ethylene glycol adduct, diethylene glycol, triethylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polytetramethylene oxide glycol, dimethylolpropionic acid, glycerin, trimethylolpropane, sodium dimethylolethylsulfonate, and potassium dimethylolpropionate can be used. One or more of these compounds can be appropriately selected from each of them, and a polyester resin can be synthesized by a conventional polycondensation reaction.

[0079] When a crosslinking agent is blended in the release layer forming composition, the content of the crosslinking agent in the release layer forming composition is preferably 5 to 98% by mass, more preferably 15% by mass or more or 90% by mass or less, even more preferably 30% by mass or more or 70% by mass or less, even more preferably 38% by mass or more or 50% by mass or less. If the content of the crosslinking agent is 5% by mass or more, the strength of the coating film can be increased, and if the content of the crosslinking agent is 98% by mass or less, there is a possibility that sufficient releasability of the release layer and adhesion to the polyester film can be ensured.

[0080] When a polymer is blended into the release layer-forming composition, the content of the polymer in the release layer-forming composition is preferably 1 to 80 mass %, more preferably 5 mass % or more or 70 mass % or less, and even more preferably 20 mass % or more or 60 mass % or less.

[0081] The coating liquid of the release layer-forming composition may be an aqueous coating liquid using water as a solvent, and in this case, may contain a small amount of an organic solvent. In this case, examples of organic solvents include alcohols such as ethanol, isopropanol, ethylene glycol, and glycerin, ethers such as ethyl cellosolve, t-butyl cellosolve, propylene glycol monomethyl ether, and tetrahydrofuran, ketones such as acetone and methyl ethyl ketone, esters such as ethyl acetate, and amines such as methylethanolamine. These can be used alone or in combination. By appropriately selecting and adding these organic solvents to the aqueous coating liquid as necessary, the stability and coatability of the coating liquid can be improved.

[0082] The release layer-forming composition may contain particles to prevent blocking or improve slippage, if necessary. In addition, it may contain defoamers, coating improvers, thickeners, organic lubricants, ultraviolet absorbers, antioxidants, foaming agents, etc.

[0083] <Physical properties of this release film>

[0084] (Film surface roughness) When used for the purpose of imparting a low gloss feel, the roughness of the release layer surface of this release film, i.e., if a release layer is formed on one side of the polyester film, the surface, in other words, the surface on one side of this polyester film, or if a release layer is formed on both sides of the polyester film, both surfaces, in other words, the average surface roughness (Ra) of both sides of the polyester film, is preferably 0.1 μm to 2.0 μm. When the average surface roughness (Ra) of the surface of the present polyester film is within the above range, a matte finish can be expressed, and by pressing this surface against an object and releasing it, the matte finish can be imparted to the surface of the object. From this viewpoint, the average surface roughness (Ra) of at least the release layer side surface of the present polyester film is preferably 0.1 μm to 2.0 μm, more preferably 0.2 μm or more or 1.0 μm or less, and even more preferably 0.3 μm or more or 0.9 μm or less. The average surface roughness (Ra) of the film surface can be measured by the measurement method described in the Examples below. Methods for adjusting the average surface roughness (Ra) of the release layer side surface to the above range include using a polyester film having a particle-containing layer, and in particular using a copolymer polyester or particles having a particle size and true specific gravity within the above-mentioned range as the material for the particle-containing layer, and adjusting the thickness of the particle-containing layer, the stretching conditions of the polyester film, and the heat treatment conditions.

[0085] In order to further improve the low gloss feeling, the release layer side surface is preferably a surface on which a large number of relatively high protrusions are formed, in other words, a surface formed at a high density. However, when looking at the numerical value of the average surface roughness (Ra) of the release layer side surface, it is necessary to note that the characteristics of the release layer side surface, that is, the characteristics of the surface on which a large number of relatively high protrusions are formed, are not very apparent in the numerical value of Ra.

[0086] In addition, if one surface of the present polyester film is matte-like, the other surface is sufficient to be roughened to an extent that handling is not hindered, and from the viewpoint of improving adhesion when laminating with other layers, it is preferable that the average surface roughness (Ra) of the other surface is smaller than that of the release layer side surface. From this viewpoint, the average surface roughness (Ra) of the other surface is preferably 0.01 μm to 1.0 μm, more preferably 0.03 μm or more or 0.8 μm or less, more preferably 0.05 μm or more or 0.5 μm or less, and even more preferably 0.1 μm or more or 0.3 μm or less.

[0087] (Glossiness) In the present polyester film, it is preferable that the gloss of at least the surface on the release layer side is 30% or less. If the gloss of the film surface is 30% or less, it can have a luxurious matte finish, with the lower limit being about 0.1%. From this viewpoint, in the present polyester film, the gloss of at least the surface on the release layer side is preferably 30% or less, more preferably 0.1% or more or 30% or less, even more preferably 25% or less, and even more preferably 20% or less.

[0088] (Surface free energy of release layer surface) In the present polyester film, the surface free energy of the release layer side surface is preferably 27 mN / m or more. If the surface free energy of the release layer surface is 27 mN / m or more, the wettability is not poor, and it is possible to process the resin layer to be transferred onto the surface of the release layer, and even if the release component is transferred, it is possible to reduce the adverse effect on the surface of the mating material. Also, if the surface free energy is 60 mN / m or less, it is possible to obtain releasability for the resin layer to be transferred. From this viewpoint, in the present polyester film, the surface free energy of the release layer surface is preferably 27 mN / m or more or 60 mN / m or less, more preferably 30 mN / m or more or 50 mN / m or less, and even more preferably 33 mN / m or more or 45 mN / m or less. Methods for adjusting the surface free energy include selection of a release agent, selection of a crosslinking agent or polymer used in combination, and adjustment of the content or content ratio of the release agent in the release layer.

[0089] (Transfer rate of release component) The present release film preferably has a transfer rate of the release component measured by the method described below of 40% or less, more preferably 35% or less, even more preferably 33% or less, and even more preferably 30% or less. If the transfer rate of the release component is 40% or less, the effect on the target surface is small, making it possible to suppress adverse effects on secondary processing.

[0090] (Initial peel strength of hard coat layer) It is preferable that the initial peel strength of the release film from the hard coat layer, measured by the method described below, is greater than the peel strength of the hard coat layer after the press treatment described below. In particular, the initial peel strength of the hard coat layer is preferably 1.1 times or more, more preferably 1.3 times or more, and particularly preferably 1.5 times or more, of the peel strength of the hard coat layer after the press treatment. If the initial peel strength of the hard coat layer is greater than the peel strength of the hard coat layer after the press treatment, it is possible to prevent the release film from peeling off before it is used in the transfer treatment.

[0091] (Peeling strength of hard coat layer after press processing) The release film preferably has a peel strength against the hard coat layer after pressing for 30 minutes under conditions of 170°C x 3 MPa, as measured by the method described below, of 100 mN / cm, more preferably 80 mN / cm or less, even more preferably 60 mN / cm or less, and even more preferably 50 mN / cm or less. If it is 100 mN / cm or less, the stress required for peeling the hard coat layer is small, making it possible to prevent defects due to poor peeling.

[0092] <Method of manufacturing the polyester film> An example of the method for producing the present polyester film will be described below, although the method for producing the present polyester film is not limited to the method described below.

[0093] First, the raw materials for each layer, i.e., the base layer, the particle-containing layer A, the particle-containing layer B, and other layers, are prepared by a known method, and each is fed to a melt extrusion device, heated to a temperature equal to or higher than the melting point of each polymer, and melt-kneaded. Then, the molten polymer of each layer is usually introduced to a die via a multi-manifold or feed block and laminated. Next, the molten sheet extruded from the die is rapidly cooled and solidified on a rotating cooling drum to a temperature below the glass transition temperature to obtain a substantially amorphous unoriented sheet. In this case, in order to improve the flatness of the sheet, it is preferable to increase the adhesion between the sheet and the rotating cooling drum, and an electrostatic application adhesion method and / or a liquid application adhesion method are preferably adopted.

[0094] Next, the obtained unstretched sheet is stretched in one direction by a roll or tenter type stretching machine. The stretching temperature is usually 70 to 150°C, preferably 80 to 140°C, and the stretching ratio is usually 2.5 to 7 times, preferably 3.0 to 6 times. Next, in the direction perpendicular to the first-stage stretching direction, the sheet is stretched at usually 70 to 170°C, and the stretching ratio is usually 2.5 to 7 times, preferably 3.0 to 6 times. Subsequently, the sheet is heat-treated under tension or relaxation of 30% or less at a temperature of 180 to 270°C to obtain a biaxially oriented film. In the above stretching, a method of stretching in one direction in two or more stages can also be adopted. In that case, it is preferable to perform the stretching so that the final stretching ratios in both directions are each within the above range.

[0095] The heat treatment after the transverse stretching is performed at a temperature higher than the melting point of the polyester containing a copolymer component, for example, in the case of a polyester containing an isophthalic acid component, the heat treatment temperature is preferably 220° C. or higher, and more preferably 230 to 250° C. When polyester A, which is the main component resin of the particle-containing layer A, is a copolymer polyester, it becomes soft by such heat treatment, and the particles rise to the surface, thereby making it possible to increase the height of the protrusions.

[0096] After the heat treatment step, it is preferable to relax the film by 2 to 20% in the longitudinal and / or transverse directions in the maximum temperature zone of the heat treatment and / or in the cooling zone at the heat treatment outlet. If necessary, it is also possible to add another longitudinal or transverse stretching.

[0097] In the above-mentioned production method, the release layer is preferably formed by coating the above-mentioned "release layer-forming composition" between the above-mentioned longitudinal stretching and transverse stretching, as described above. In this way, coating can be performed simultaneously with stretching, and the thickness of the release layer can be made thin according to the stretching ratio, so that a film suitable as a polyester film can be produced.

[0098] <How to use this release film> This release film can be used for simultaneous molding transfer, in which a resin layer such as a hard coat layer is provided on the release layer surface to form a transfer foil, which is then set in a mold for injection molding, and the transfer foil is integrated and adhered at the same time as the resin molded product is formed, thereby transferring the foil to the resin molded product. Furthermore, the release layer can be pressed against the surface of an object such as a hard coat layer and then the release film can be peeled off, thereby transferring the surface shape of the release layer to the surface of the object. In addition, by designing the release layer side of the polyester film to have a low gloss, the roughened surface shape of the release layer surface can be transferred, and the low gloss of the release layer surface can be imparted to the product surface. In this case, the product surface can be, for example, an electromagnetic wave shielding film or a transfer foil for simultaneous molding transfer, particularly the hard coat layer surface thereof. However, it is not limited to these. Therefore, the present release film can be suitably used for applications such as transferring a transfer foil consisting of a resin layer such as a hard coat layer onto a resin molded product, that is, as a transfer release film for simultaneous transfer and decoration during molding. In addition, the release film can also be suitably used for the purpose of imparting a low gloss feeling to the surface of various members, such as electromagnetic wave shielding members, by transferring the shape of the release layer side surface of the release film to the surface of the member, i.e., as a release film for transferring surface shapes.

[0099] <Explanation of terms> In this specification, when expressed as "X to Y" (X and Y are arbitrary numbers), unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as "preferably larger than X" or "preferably smaller than Y". In addition, when it is expressed as "X or more" (X is any number) or "Y or less" (Y is any number), it also includes the intention that "greater than X is preferable" or "less than Y is preferable." EXAMPLES

[0100] The present invention will now be described in further detail with reference to the following examples and comparative examples. First, methods for measuring and evaluating various physical properties in the following examples and comparative examples will be described. In the examples and comparative examples, "parts" refers to "parts by mass." The measurement methods used in the present invention are as follows.

[0101] (1) Intrinsic viscosity of polyester 1 g of polyester from which components incompatible with the polyester had been removed was precisely weighed, dissolved in 100 ml of a mixed solvent of phenol / tetrachloroethane = 50 / 50 (mass ratio), and measured at 30°C.

[0102] (2) Average particle size The average particle size of the particles was calculated by measuring the diameters of 10 or more particles using a scanning electron microscope (SEM) and taking the average value. In the case of non-spherical particles, the average value of the longest and shortest diameters was taken as the diameter of each particle.

[0103] (3) Average surface roughness (Ra) It was determined as follows using a surface roughness measuring instrument (SE-3500) manufactured by Kosaka Laboratory Co., Ltd. That is, a portion of reference length L (2.5 mm) was cut out from the film cross-sectional curve in the direction of the average line, and when the average line of this cut out portion is expressed as the x-axis and the direction of the longitudinal magnification as the y-axis, as a roughness curve y=f(x), the value given by the following formula is expressed in [nm]. The arithmetic mean roughness was expressed as the average value of the arithmetic mean roughness of the cut out portions obtained from 10 roughness curves obtained from the sample film surface. The tip radius of the stylus was 2 μm, the load was 30 mg, and the cutoff value was 0.08 mm. Ra = (1 / L)∫ L 0|f(x)|dx

[0104] (4) Glossiness of the film surface The 60 degree gloss was measured according to the method of JIS Z-8741 using a glossmeter (VG-107 type) manufactured by Nippon Denshoku Co., Ltd. The reflectance of the sample was calculated based on the reflectance of a black standard plate at an incident angle and reflection angle of 60 degrees, and this was taken as the gloss.

[0105] (5) Ratio of release agent in the release layer The content ratio of the release agent in the release layer was calculated by the following method. Each material constituting the release layer was heated in an air atmosphere at a heating rate of 50°C / min using a differential thermal / thermogravimetric analyzer (Shimadzu Corporation DTG-60A), and the weight loss rate after holding at 240°C for 3 minutes was measured. The content of each component in the release layer-forming composition was multiplied by the obtained weight loss rate to obtain the content of each component in the release layer. The content ratio of the release agent in the obtained content of each component was obtained.

[0106] (6) Release agent content in the release layer The content of each component in the release layer was determined by the same method as in (5). The weight loss rate of the entire release layer-forming composition was calculated from the sum of these, and the amount of the release layer was calculated by multiplying it by the amount of the release layer applied. The content of the release agent in the release layer was calculated from the amount of the release layer obtained and the content ratio of the release agent in the release layer.

[0107] (7) Surface free energy of the release layer surface The contact angles of the release layer surface of the film sample that had been conditioned for 24 hours or more in an environment of 23°C and 50% RH were measured using an automatic contact angle meter (DataPhysics, model OCA20) to measure the static contact angles of water and methylene iodide. Using the obtained contact angles and the surface tension component values ​​of each solvent (Table 1), the surface free energy of the release layer surface was calculated according to the Owens-Wendt theoretical formula.

[0108] [Table 1]

[0109] (8) Transfer rate of release component The release layer side surface of the film sample was placed in contact with the untreated surface of a test polyester film (Mitsubishi Chemical Corporation, T100, thickness 50 μm) and the two films were placed together, and then heat pressed for 30 minutes under conditions of 170°C x 1 MPa, and then humidified in an environment of 23°C x 50% RH. The film sample was then removed, and the tape peeling force (F1) was measured for the surface of the test polyester film that had been in contact with the release layer. The polyester films obtained in Comparative Examples 1 and 2 were subjected to the same test, and the tape peel strengths (F01) and (F02) of the test polyester film surfaces were measured. For the polyester film obtained in Comparative Example 2, the two films were superimposed so that the surface of the particle-containing layer A was in contact with the untreated surface of the test polyester film, and then hot-pressed. In Examples 1 and 2, the transfer rate was calculated from the formula: transfer rate (%)=(F01-F1) / F01×100. For Examples 3 to 22 and Comparative Examples 3 to 6, the transfer rate was calculated from the formula: transfer rate (%)=(F02-F1) / F02×100. In Comparative Examples 1 and 2, the transfer rate was set to zero. The tape peeling force was measured by attaching an acrylic adhesive tape ("No. 31B" manufactured by Nitto Denko Corporation) to this release layer, leaving it at room temperature for 1 hour, and then peeling it off in a 180° direction at a tensile speed of 0.3 m / min.

[0110] (9) Peel strength of hard coat layer (initial) A hard coat composition was prepared by mixing 15-functional urethane acrylate (U-15HA manufactured by Shin-Nakamura Chemical Co., Ltd.), pentaerythritol triacrylate mixture (PET-3 manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), and photopolymerization initiator (Omnirad184 manufactured by IGM Resins BV) in a ratio of 70:30:5, and dissolved in methyl ethyl ketone (MEK). The hard coat composition was applied to the release layer to a dry thickness of 5 μm, dried, and then exposed to 300 mJ / cm under a high-pressure mercury lamp. 2 The hard coat layer was formed on the release film by curing at 40° C. After that, a 24 mm wide cellophane tape (LP-24, manufactured by Nichiban Co., Ltd.) was attached to the surface of the hard coat, and the stress was measured when the release film was peeled off in a 180° direction at a pulling speed of 1000 mm / min.

[0111] (10) Peel strength of hard coat layer (after press treatment) The release film with the hard coat layer prepared in (9) was pressed for 30 minutes under conditions of 170°C x 3 MPa. After that, the stress when peeling off this release film was measured using the same method as the initial peel force. If the hard coat layer could not be peeled off from the release film, it is recorded as "unpeelable", and if the resin was repelled during the formation of the hard coat layer and the hard coat layer could not be formed, it is recorded as "unprocessable".

[0112] The polyesters used in the examples and comparative examples were prepared as follows.

[0113] <Polyester (A)> A polyethylene terephthalate homopolymer with an intrinsic viscosity of 0.63 dl / g.

[0114] <Polyester (B)> A polyethylene terephthalate homopolymer having an intrinsic viscosity of 0.65 dl / g and containing 0.2% by mass of silica particles with an average particle size of 2 μm.

[0115] <Polyester (C)> A polyethylene terephthalate homopolymer having an intrinsic viscosity of 0.61 dl / g and containing 10% by mass of alkyl methacrylate-styrene copolymer particles (true specific gravity: 1.1) with an average particle size of 4.5 μm.

[0116] <Polyester (D)> A copolymerized polyethylene terephthalate polymer containing 22 mol% isophthalic acid, having an intrinsic viscosity of 0.70 dl / g and a melting point of 198°C.

[0117] The compounds used in forming the release layer are as follows:

[0118] <Release agent (IA)> A water dispersion of oxidized polyethylene wax (melting point 125°C).

[0119] <Release agent (IB)> A water dispersion of modified polypropylene wax (melting point 156°C).

[0120] <Release agent (IC)> A long-chain alkyl group-containing compound in which octadecyl isocyanate is added to polyvinyl alcohol with an average degree of polymerization of 500 and a degree of saponification of 88 mol%.

[0121] <Polyester resin (II)> A water dispersion of polyester resin copolymerized in the following ratios: (acid components) terephthalic acid / isophthalic acid / 5-sodium sulfoisophthalic acid / / (diol components) ethylene glycol / 1,4-butanediol / diethylene glycol = 56 / 40 / 4 / / 70 / 20 / 10 (mol %).

[0122] <Melamine compounds (III)> Partially etherified melamine having a methylol group, a methoxy group and an imino group.

[0123] <Example 1> A mixed raw material (particle content 0.02% by mass) of polyesters (A) and (B) mixed at a ratio of 90% by mass and 10% by mass, respectively, was used as the raw material for the outermost layer (surface layer), and only polyester (A) was used as the raw material for the intermediate layer. Each was fed to two extruders, melted at 285 ° C., and then co-extruded on a cooling roll set at 40 ° C. with a layer structure of two types and three layers (surface layer / intermediate layer / surface layer = 1: 8: 1 discharge amount) and cooled and solidified to obtain an unstretched sheet. Next, the film was stretched 3.4 times in the longitudinal direction at a film temperature of 85 ° C. using the roll peripheral speed difference, and then a release layer forming composition having the composition shown in Table 2 below was diluted with water and applied as coating liquid 1 on one side of this longitudinally stretched film, which was introduced into a tenter, stretched 4.3 times in the transverse direction at 110 ° C., and heat-treated at 235 ° C., and then relaxed by 2% in the transverse direction. The coating amount (after drying) was 150 mg / m 2 Thus, a release film (sample) having a thickness of 50 μm and a release layer of the above composition was obtained. The properties of this release film (sample) are shown in Table 3 below.

[0124] <Example 2> In Example 1, the composition of the release layer-forming composition was changed to the composition shown in Table 2, and the coating amount (after drying) was 200 mg / m 2 A polyester film (sample) was obtained in the same manner as in Example 1, except for changing the above. The properties of the obtained release film (sample) are shown in Table 3. The release films (samples) of all the Examples had a low transfer rate of the release component and excellent releasability.

[0125] <Example 3> A mixture of polyesters (A), (C), and (D) blended at 20 mass%, 60 mass%, and 20 mass%, respectively (particle content 6 mass%, copolymerization component amount 4.4 mol%) was melted in an extruder and supplied to the surface layer (particle-containing layer A) of the laminated die, while polyester (A) was supplied to the base layer of the laminated die, and a mixture of polyesters (A), (C), and (D) blended at 80 mass%, 10 mass%, and 10 mass%, respectively (particle content 1 mass%, copolymerization component amount 2.2 mol%) was supplied to the other surface layer (particle-containing layer B) of the laminated die, and a three-layer laminated polyester resin consisting of three types and three layers (particle-containing layer A / base layer / particle-containing layer B = 1:8:1 ratio) was extruded into a film shape, and cooled and solidified on a cooling roll at 35 ° C. to prepare an unstretched sheet. Next, after preheating with a heating roll at 80°C, the film was stretched 3.2 times in the longitudinal direction between rolls at 95°C using an infrared heater and a heating roll in combination, and then a release layer-forming composition having the composition shown in Table 2 below, diluted with water, was applied to one side of this longitudinally stretched film as coating liquid 1. The film was then guided into a tenter while holding the ends of the film with clips, and stretched 4.2 times in the transverse direction while being heated at a temperature of 110°C. Heat treatment was then performed at 240°C for 10 seconds, and at the same time, relaxation was performed by 10% in the width direction, so that the coating amount (after drying) was 150 mg / m 2 Thus, a release film (sample) having a thickness of 50 μm (particle-containing layer A / base layer / particle-containing layer B=5 μm / 40 μm / 5 μm) was obtained.

[0126] <Examples 4 to 22> In Example 3, the composition of the release layer forming composition was changed to the composition shown in Table 2, and the coating amount (after drying) was changed to the composition shown in Table 3. Except for this, the same production process as in Example 3 was carried out to obtain a release film (sample). The properties of the obtained release film (sample) are shown in Table 3. The release films (samples) of all the Examples had good average surface roughness (Ra) and gloss, appropriate surface free energy, a low transfer rate of the release component, and good releasability.

[0127] <Comparative Example 1> A polyester film (sample) was obtained in the same manner as in Example 1, except that no release layer was provided. The properties of the obtained polyester film (sample) are shown in Table 3. As shown in Table 3, the hard coat layer could not be peeled off.

[0128] <Comparative Example 2> A polyester film (sample) was obtained in the same manner as in Example 3, except that no release layer was provided. The properties of the obtained polyester film (sample) are shown in Table 3. As shown in Table 3, the hard coat layer could not be peeled off.

[0129] <Comparative Examples 3 to 6> In Example 3, the composition of the release layer forming composition was changed to the composition shown in Table 2, and the coating amount (after drying) was changed to the composition shown in Table 3. Except for this, the same production process as in Example 3 was carried out to obtain a release film (sample). The properties of the obtained release film (sample) are shown in Table 3. As shown in Table 3, there were cases where a large amount of the release component was transferred and cases where the hard coat layer was impossible to peel off.

[0130] [Table 2]

[0131] [Table 3]

[0132] From the results of the above examples and the results of tests conducted by the present inventors, it is found that the release agent accounts for less than 15 mass % of the total non-volatile components in the release layer-forming composition, and the content of the release agent in the release layer is 3.4 mg / m 2 It was found that if the thickness is equal to or greater than this, the release properties are excellent and the amount of transfer of the release component can be reduced. [Industrial Applicability]

[0133] Since the present release film has an appropriate content ratio and amount of the release agent, it has excellent release performance and also has excellent secondary processability onto the object of transfer, and therefore can be suitably used as a release film for transfer, particularly for surface shape transfer onto electromagnetic wave shielding materials, etc., and simultaneous molding transfer.

Claims

1. A release layer formed from a release layer-forming composition is provided on at least one side of a polyester film, the release agent is contained in the release layer-forming composition in an amount of 9% by mass or less as a proportion of the total non-volatile components, and the content of the release agent in the release layer is 3.4 mg / m 2 or more and 11.5 mg / m 2 or less.

2. A release film comprising a release layer on at least one side of a polyester film, said release layer containing no more than 10 mass % of a release agent, and said release layer having a release agent content of 3.4 mg / m2 or more and 11.5 mg / m2 or less.

3. A release film as described in claim 1 or 2, wherein the peel strength from the hard coat layer after pressing for 30 minutes under conditions of 170°C x 3 MPa, as measured by the following measurement method, is 100 mN / cm or less. <Method for measuring peel strength> A hard coat composition obtained by mixing 15-functional urethane acrylate (U-15HA manufactured by Shin-Nakamura Chemical Co., Ltd.), pentaerythritol triacrylate mixture (PET-3 manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), and photopolymerization initiator (Omnirad 184 manufactured by IGM Resins B.V.) in a ratio of 70:30:5 was applied onto the release layer of the release film so as to have a dry thickness of 5 μm, and after drying, the composition was cured under a high-pressure mercury lamp at 300 mJ / cm 2 to prepare a release film with a hard coat layer. A 24 mm wide cellophane tape (registered trademark) (LP-24 manufactured by Nichiban Co., Ltd.) is attached to the surface of the hard coat layer, and a press treatment is performed for 30 minutes under conditions of 170°C x 3 MPa. After that, the release film is peeled off in a 180° direction at a tensile speed of 1000 mm / min, and the stress is measured.

4. A release film as described in claim 3, wherein the initial peel force of the hard coat layer is greater than the peel force of the hard coat layer after pressing for 30 minutes under conditions of 170°C x 3 MPa using the measurement method.

5. A release film described in any one of claims 1 to 4, wherein the surface free energy of the release layer side surface is 27 mN / m or more.

6. A release film described in any one of claims 1 to 5, wherein the release agent is a wax.

7. A release film described in any one of claims 1 to 6, wherein the release layer contains a compound derived from a crosslinking agent.

8. A release film described in any one of claims 1 to 7, wherein the average surface roughness (Ra) of the release layer side surface is 0.1 μm to 2.0 μm.

9. A release film described in any one of claims 1 to 8, wherein the gloss of the surface on the release layer side is 30% or less.

10. A release film described in any one of claims 1 to 9, wherein the transfer rate of the release component is 40% or less, as measured by the following measurement method. <Method for measuring transfer rate of release component> The release layer side surface of the release film sample and the surface of the polyester film for measurement test (T100, thickness 50 μm, manufactured by Mitsubishi Chemical Corporation) that has not been surface-treated are stacked together, and the two films are heat-pressed under conditions of 170° C.×1 MPa for 30 minutes, and then humidified under an environment of 23° C.×50% RH. The release film sample is then removed, and the tape peeling force (F1) is measured for the surface of the polyester film for measurement test that was in contact with the release layer. The same measurement as above is carried out on the release film sample not provided with a release layer, and the tape peeling force (F0) is measured. The tape peeling force is the stress when an acrylic adhesive tape (manufactured by Nitto Denko Corporation, "No. 31B") is attached to the surface of the polyester film for measurement test that was in contact with the release layer, or to the surface of the release film sample that does not have a release layer, and then left at room temperature for 1 hour, and then peeled in a 180° direction at a tensile speed of 0.3 m / min. The transfer rate (%) is calculated from the tape peeling forces (F1) and (F0) according to the following formula. Transfer rate (%) = {(F0-F1) / F0}×100

11. A release film described in any one of claims 1 to 10, wherein the polyester film has a particle-containing layer containing particles, and the average particle size of the particles is 2.0 to 10.0 μm.

12. A release film as described in claim 11, wherein the true specific gravity of the particles is 2.0 or less.

13. A release film as described in claim 11 or 12, wherein the particle-containing layer contains a copolymer component at 0.1 to 10 mol % relative to the polyester constituting the particle-containing layer.

14. A transfer release film comprising the release film according to any one of claims 1 to 13.